INSTITUTE OF LATIN AMERICAN ART (IAL): CRITICAL AND ARTISTIC DEBATES (1970-1973). TOWARDS A SOCIALIST ART. - Cofré Cubillos , Claudia (2022)
During the Popular Unity (UP) in Chile, a global transformation of society was conceived, which included cultural action as a means to overcome “underdevelopment” and dependency. In this context, a series of exhibitions, exchanges and networks between Latin American artists, as well as important debates on the condition of art and the artist’s attitude within the society of the time took place. Thus, a culture of transition to socialism develops, influenced by the political conditions in which the UP was created. This text makes a panoramic tour of the different critical and artistic topics and debates—circumscribed in the Institute of Latin American Art of the University of Chile—that were part of the cultural development of the UP. The aim is to offer both a diagnosis and a critical map of the work of the artists in a revolutionary context of transition to socialism, thus intending to contribute to the rescue of our artistic and cultural history.